Value of the peripheral blood smear as a diagnostic guide in hemolytic anemia - Nelson Rafael Terry Leonard; Carlos A. Mendoza Hernández (Medisur)
Hemolytic anemia is a group of disorders in which there is an early destruction of the red blood cell. The group of clinical manifestations derived from this hemolysis is known as hemolytic syndrome, in which the results of the peripheral lamina vary according to the cause of the hemolysis, reason why this examination constitutes a valuable orientation. This bibliographical review addresses the results of the peripheral blood smear study in different causes of hemolytic anemia and describes the morphological and semi-quantitative alterations of peripheral blood cells with the aim of providing a guideline that suggests an early diagnosis due to the seriousness of some conditions of hemolytic syndrome.